(untitled) (Довкілля та здоров’я, 2022)
Objective: The aim of our work was to study the potential ecotoxicological hazard of a new chemical from the class of tetramic and tetronic acid derivatives - the insecticide spiromesifen, taking into account its physico-chemical properties and impact on the environmental objects. Materials and methods: An assessment of the potential danger of spiromesifen use for ecosystems was carried out on the basis of the calculation of the ecotoxicological hazard (ecotox) by N.N. Melnikov’s method. The field studies were carried out in different agro-climatic zones of Ukraine. The treatment of vineyards and apple trees was carried out at the maximum consumption rates of spiromesifen. Results: According to the literary data and our research, it was found that in the soil-and-climatic conditions of Ukraine, the ecotoxicological risk, when using the new insecticide spiromesifen, is 10,000 times and 7,000 times low than the analogous characteristics of DDT. Ecotox abamectin is 154 times low than ecotox DDT. This makes preparations, based on these substances, more promising and competitive among other pesticides in agricultural use. We can conclude that spiromesifen does not pose a threat to terrestrial ecosystems and health of the population.